2018
DOI: 10.1136/neurintsurg-2017-013641
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with a temporary bridging device (Comaneci) in the endovascular treatment of ruptured wide neck aneurysms

Abstract: The Comaneci device offers a new promising and reliable technique that can safely support aneurysm coiling occlusion even in a rupture environment. However, long term monitoring of patients treated by this device is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 19 publications
2
17
1
Order By: Relevance
“…However, no device-related complications were recorded in our initial and early experience with this new temporary bridging device. 9 This is valid also for this particular case.…”
Section: Discussionsupporting
confidence: 52%
“…However, no device-related complications were recorded in our initial and early experience with this new temporary bridging device. 9 This is valid also for this particular case.…”
Section: Discussionsupporting
confidence: 52%
“…It is important to emphasize that these observations are based only on personal opinion and do not represent statistically validated conclusions. As noted during the initial experience with Comaneci, deflection of the device (and particularly its distal tip) can produce significant nearly occlusive spasm during expansion 8. We did not observe this phenomenon in the present case series with the Cascade.…”
Section: Discussioncontrasting
confidence: 38%
“…One such method is the placement of a temporal neck bridging device, which allows parent vessel flow during intrasaccular embolization 6. Recent clinical experience with the Comaneci temporal neck bridging device demonstrated that this methodology can result in satisfactory and durable embolization 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Comaneci device comes in three different sizes: (1) Comaneci is 32 mm in net length and expands to 4.5 mm in diameter; (2) Comaneci Petit is 24 mm in net length and expands to 3.5 mm; and (3) Comaneci 17 is 22 mm in net length and expands to 3.0 mm 35. Sirakov et al 36 2018 described their experience with Comaneci in treating ruptured wide-neck aneurysms. Complete occlusion was achieved in 86% (25/29) of the patients, and only one patient had possibly procedure-related complications, thus supporting the use of Comaneci in treating ruptured aneurysms.…”
Section: Advances In Stent-assisted Coilingmentioning
confidence: 99%